2015
DOI: 10.1080/00048623.2015.1063800
|View full text |Cite
|
Sign up to set email alerts
|

‘Cultural Competence is for Everyone’: Cultural Competence in the United States Library and Information Sector. Is It Relevant to Australian Libraries?

Abstract: Cultural competence is a capacity that enables professionals and organisations to work effectively in cross-cultural situations. It has been adopted in fields such as health, social work, psychology, education and information. Library and information science in the USA has responded to growing diversity in the population by incorporating cultural competence into policy, education and practice. This article traces how this has occurred, likening the process to a learning cycle or virtuous circle. Similarities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The first area relates to the concept of cultural and linguistic expertise as a deficit or skills gap among library personnel. Solutions to this deficit have focused on LIS education and training, policy development, community outreach, recruiting methods, marketing, ethnic informational profiling and the notion of 'cultural competence' (Black, 2018;Blackburn, 2015aBlackburn, , 2015bBlackburn, , 2020Clifton, 2019;Du, Tan, & Xu, 2019;Foster, 2018;Hernandez & Field, 2003;Hill, 2018;Khoir, Du, Davison, & Koronios, 2017;Kumasi & Hill, 2013;Mestre, 2010). The second area of long-standing and ongoing concern is the impasse between the professional standards and practices that form the epistemic and epistemological foundations of LIS knowledge and education and the growing body of critical LIS knowledge and expanding movements of 'epistemic disobedience' (Mignolo, 2009, pp.…”
Section: Talking About Diversity Againmentioning
confidence: 99%
“…The first area relates to the concept of cultural and linguistic expertise as a deficit or skills gap among library personnel. Solutions to this deficit have focused on LIS education and training, policy development, community outreach, recruiting methods, marketing, ethnic informational profiling and the notion of 'cultural competence' (Black, 2018;Blackburn, 2015aBlackburn, , 2015bBlackburn, , 2020Clifton, 2019;Du, Tan, & Xu, 2019;Foster, 2018;Hernandez & Field, 2003;Hill, 2018;Khoir, Du, Davison, & Koronios, 2017;Kumasi & Hill, 2013;Mestre, 2010). The second area of long-standing and ongoing concern is the impasse between the professional standards and practices that form the epistemic and epistemological foundations of LIS knowledge and education and the growing body of critical LIS knowledge and expanding movements of 'epistemic disobedience' (Mignolo, 2009, pp.…”
Section: Talking About Diversity Againmentioning
confidence: 99%
“…In Australian libraries, a recent trend at an institutional level is to adopt 'diversity' and 'inclusion' policies and plans in an apparent attempt to better recognise and reflect Australia's social pluralism in collections, programs, and workforces. Such initiatives, including 'cultural competence' training in LIS education and the workplace, have formed the focus of two recent journal articles in Australian LIS scholarship (Blackburn, 2015;Maestro et al, 2018). Critical race scholars, as well as critical librarians, have suggested that institutional commitments to 'diversity' perform a largely symbolic function that do little to disrupt institutional racism and white dominance.…”
Section: 'Multiculturalism' In Lis Scholarship: From Valorisation To Critiquementioning
confidence: 99%
“…Enrolling in a Master of Information Management course, I researched library and information science and cultural competence (Blackburn, 2015). I came to consider cultural competence fundamental to cross-cultural provision and community engagement: both entail working from a library’s particular way of operating (its culture), with groups having other cultures.…”
Section: Approachmentioning
confidence: 99%